Ensemble based quantum memory and adiabatic phase gates in electron spins - Wu, H (2011)
Quantum computing has been a new and challenging area of research since the concept was put forward in 1980s. A quantum computer is a computer that processes information encoded in systems that exhibit quantum properties and is proved in theory to be more powerful than classical computers. Various approaches to the implementation of the quantum computers have been studied over the decades, each of them having their own advantages and disadvantages in terms of the lifetime of the quantum information, processing time, and scalability of the implementation. Proposals for hybrid quantum processors are interesting because they benefit from the advantages of each comprising system, and thus providing a promising approach to a practical quantum computer. In this thesis, I demonstrate experimentally the principle of utilizing electron spin ensembles as a quantum memory for hybrid quantum processors. I demonstrate the storage and on-demand retrieval of multiple bits of quantum information into and from a single electron spin ensemble by applying magnetic field gradient pulses. I then study the coupling between an electron spin ensemble and a three-dimensional microwave cavity, in the aim of discussing the condition for the coherent information transfer between the excitations in solid-state matter and photons. As an alternative to the high power pulses in electron paramagnetic resonance (EPR), I study the possibility of controlling the electron spin states via adiabatic processes. I demonstrate the implementation of adiabatic geometric phase gates in electron spins and compare their performances to other phase gates achieved with microwave pulses in both simulation and experiment, verifying the robustness of the adiabatic gates against certain type of noises. Finally I present the simulation method developed for simulating the pulsed EPR experiments in this thesis, using a model more general than some currently-existing simulation packages.